Topics on system analysis and integrated water resource management - Castelletti, Andrea; Soncini Sessa, Rodolfo
The Integrated Water Resources Management (IWRM) paradigm has been worldwide recognized as the only feasible way currently available to ensure a sustainable perspective in planning and managing water resource systems. It is the inspiring principle of the Water Framework Directive, adopted by the European Union in 2000, as well as the main reference for all the water related activity of UNESCO in the third world countries. However, very often, real world attempts of implementing IWRM fail for the lack of a systematic approach and the inadequacy of tools and techniques adopted to address the intrinsically complex nature of water systems. This book explores recent and important contributions of System Analysis and Control Theory to the technical application of such paradigm and to the improvement of its theoretical basis. Its prior aim is to demonstrate how the modelling and computational difficulties posed by this paradigm might be significantly reduced by strengthening the efficiency of the solution techniques, instead of weakening the integration requirements. The first introductory chapter provides the reader with a logical map of the book, by formalizing the IWRM paradigm in a nine-step decisional procedure and by identifying the points where the contribution of System Analysis and Control Theory is more useful. The book is then organized in three sections whose chapters analyze some theoretical and mathematical aspects of these contributions or presents design applications. The outstanding research issues on the border between System Analysis and IWRM is depicted in the last chapter, where a pull of scientists and experts, coordinated by Prof. Tony Jakeman describe the foreseeable scenario. The book is based on the most outstanding contributions to the IFAC workshop on Modelling and Control for Participatory Planning and Managing Water Systems held in Venice, September 28- October 1, 2004. That workshop has been conceived and organized with the explicit purpose of producing this book: the maximum length of the papers was unusually long (of the size of a book chapter) and only five long oral presentations were planned each day, thus allowing for a very useful and constructive discussion. - Contributions from the leading world specialists of the field - Integration of technical modelling aspects and participatory decision-making - Good compromise between theory and application.